Effect of antibiotics on short-term growth among children in Burkina Faso: a randomized trial - Sié, Ali; Bärnighausen, Till (The American journal of tropical medicine and hygiene, 2018)
Antibiotics improve both weight and height gain in randomized trials of preschool children with preexisting morbidity. Here, we assess the effect of a short course of three different antibiotics (amoxicillin, azithromycin, and cotrimoxazole) on short-term linear and ponderal growth in a population-based sample of preschool children in rural Burkina Faso. We randomized households with at least two children in the Nouna district, Burkina Faso, to a 5-day course of amoxicillin, azithromycin, cotrimoxazole, or placebo. Within each antibiotic-randomized household, one child was randomly assigned to receive the antibiotic and the other to receive the placebo. Weight and height measurements were taken at baseline and 30 days following the last study medication dose. Weight-for-height Z (WHZ), height-for-age Z (HAZ), and weight-for-age Z (WAZ) scoreswere calculated based on the 2006 World Health Organization standards. Of the 124 households and 248 children enrolled, 229 had anthropometry measurements at 1 month and were analyzed. Children randomized to amoxicillin gained significantly more weight compared with both the placebo household (mean difference 317 g, 95% confidence interval [CI]: 115-519 g) and placebo sibling (mean difference 315 g, 95% CI: 147-482 g) controls. Growth velocity in g/kg/day, and WHZ and WAZ scores were higher in amoxicillin-treated children compared with placebo households and siblings. There were no differences in weight gain in children randomized to azithromycin or cotrimoxazole compared with placebo households or placebo siblings. There were no differences in height gain or HAZ across any of the study arms. Amoxicillin may have short-term growth-promoting effects in healthy children.
Gesehen am 24.09.2019